Existence of solutions to nonlinear parabolic equations via majorant integral kernel. (October 2022) - Ishige, Kazuhiro; Kawakami, Tatsuki; Okabe, Shinya
Abstract: We establish the existence of solutions to the Cauchy problem for a large class of nonlinear parabolic equations including fractional semilinear parabolic equations, higher-order semilinear parabolic equations, and viscous Hamilton–Jacobi equations by using the majorant kernel introduced in Ishige et al. (2020).